1974
DOI: 10.1111/j.1365-246x.1974.tb04110.x
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Heat Flow and Heat Generation in South-west England

Abstract: Three heat flow values for south‐west England are presented. Two of the sites, Geevor and South Crofty, are operating tin mines on the northern contacts of the Land's End and Carnmenellis Granites, respectively, while the third, Wilsey Down, is a stratigraphical borehole 5 km north of the Bodmin Moor Granite. After applying topographic corrections values of 128·6 mW m‐2 (3·07 μ cal cm‐2 s‐1) for Geevor, 128·9 mW m‐2 (3·08 (A cal cm‐2 s‐1) for South Crofty and 67·3 mW cm‐2 (1·61 cal cm‐2 s‐1) for Wilsey Down, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…James (1944) showed that temperature gradients are very high in the mines of the Cornubian Peninsula; excluding one much lower value, the range of 20 values that he quoted was from 24 to 76ºCkm -1 , averaging 43ºCkm -1 . Tammemagi and Wheildon (1974) reported corrected heat flow values in granites of 134.8 mWm -2 at the Geevor Mine (Land's End pluton) and 137.7 mWm -2 at the South Crofty Mine (Carnmenellis pluton). Those authors suggested that the high heat flow could be related to the convection of hydrothermal fluids in the belt of mineralization that runs from Land's End past the northern end of the Carnmenellis pluton, in which the measurements were made.…”
Section: Geophysical Properties Of the Cornubian Granitesmentioning
confidence: 99%
“…James (1944) showed that temperature gradients are very high in the mines of the Cornubian Peninsula; excluding one much lower value, the range of 20 values that he quoted was from 24 to 76ºCkm -1 , averaging 43ºCkm -1 . Tammemagi and Wheildon (1974) reported corrected heat flow values in granites of 134.8 mWm -2 at the Geevor Mine (Land's End pluton) and 137.7 mWm -2 at the South Crofty Mine (Carnmenellis pluton). Those authors suggested that the high heat flow could be related to the convection of hydrothermal fluids in the belt of mineralization that runs from Land's End past the northern end of the Carnmenellis pluton, in which the measurements were made.…”
Section: Geophysical Properties Of the Cornubian Granitesmentioning
confidence: 99%
“…Anomalously high heat flow values based on temperature measurements made at various levels in two mines, have been reported from South-west England (Tammemagi & Wheildon 1974). It is the purpose of ihis study to verify the above results utilizing data obtained from surface exploration boreholes, and also to further delineate the zone of high heat flow.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivities were measured on core samples from boreholes 0, P, E and BKML4 using a divided-bar apparatus and standard techniques (see Tammemagi & Wheildon 1974, for details) and the results are depicted in Fig. 3 .…”
Section: Conduc-heatmentioning
confidence: 99%
“…The two mine sites (South Crofty: SCM and Geevor: GM) both produce anomalously high heat flows. Tammemagi and Wheildon (1974) report that the temperature measurements were made in horizontal and inclined boreholes at various levels throughout the mines. They discussed the possibility that the extensive period of mining would have led to disturbed temperatures in the mine that might have affected virgin rock temperatures.…”
Section: Heat Flowmentioning
confidence: 99%
“…It was recognised that this could cause problems due to ground water flow, deep weathering and recent climate change. These data were supplemented by measurements in mines at South Crofty and Geevor, where access to much greater depths was possible (Tammemagi and Wheildon 1974). These combined results were published in summaries of the UK heat flow (Lee 1986;Lee et al 1987) and it is these publications which have been widely cited when referencing these data.…”
Section: Introductionmentioning
confidence: 99%